Modulatory Effect of Low-Intensity Transcranial Ultrasound Stimulation on Behaviour and Neural Oscillation in Mouse Models of Alzheimer’s Disease - Huifang Yang; Jiaqing Yan; Hui Ji; Mengran Wang; Teng Wang; Huiling Yi; Lanxiang Liu; Xin Li; Yi Yuan (IEEE Transactions on Neural Systems and Rehabilitation Engineering, 2024)
Transcranial ultrasound stimulation (TUS) is a noninvasive brain neuromodulation technique. The application of TUS for Alzheimer’s disease (AD) therapy has not been widely studied. In this study, a long-term course (28 days) of TUS was used to stimulate the hippocampus of APP/PS1 mice. We examined the modulatory effect of TUS on behavior and neural oscillation in AD mice. We found that TUS can 1) improve the learning and memory abilities of AD mice; 2) reduce the phase-amplitude coupling of delta-epsilon, delta-gamma and theta-gamma frequency bands of local field potential, and increase the relative power of epsilon frequency bands in AD mice; 3) reduce the spike firing rate of interneurons and inhibit the phase-locked angle deflection between the theta frequency bands and the spikes of the two types of neurons that develops with the progression of the disease in AD mice. In summary, we demonstrate that TUS could effectively improve cognitive behavior and modulate neural oscillation with AD.